Bioscrew of Green Mussel (Perna viridis) Shells-derived Hydroxyapatite, Polylactic Acid and Polycaprolactone Increases Procollagen 1 Intact N-Terminal Propeptide and Alkaline Phosphatase in Rabbit Model with Bone Defect - Kartika Dwi Aprisia; Eriawan Agung Nugroho; Meita Hendrianingtyas; Robin Novriansyah; Yora Nindita; Kevin Christian Tjandra; Danendra Rakha Putra Respati; Fitri Mutmainnah; Ferry Sandra (The Prodia Education and Research Institute (PERI), 2025)
BACKGROUND: Hydroxyapatite (HA) is essential for bone regeneration and healing. Green mussel (Perna viridis) shell is a potential choice for preparing HA because they are abundant, widely available, have a smaller particle size, and have a higher HA content. Rather than using HA in powder or granule form, bioscrew has been fabricated as a composite of green mussel shell-derived HA, polylactid acid and polycaprolactone. However, its dynamic bone healing process has not been clearly disclosed, therefore Procollagen 1 Intact N-Terminal Propeptide (P1NP) and bone Alkaline Phosphatase (ALP) were investigated.METHODS: Male New Zealand white rabbits (Oryctolagus cuniculus) were used as animal model. The rabbits were anesthetized and prepared for surgery. A standardized defect was created in the metaphyseal region. For the treatment group, the defect was filled with a bioscrew implant, whereas the control group did not receive any implant. At week-2, -4 and -6 post-surgery, about 3 mL of blood was collected from rabbits' marginal ear vein to collect blood serum. The serum was used to quantify P1NP and ALP levels using Enzyme-linked Immunosorbent Assay (ELISA). Data of P1NP and ALP levels were then statistical analyzed.RESULTS: P1NP level of the treatment group was significantly (p<0.05) higher than the one of control group since the first monitor, at week-2. At the next monitor (week 4 and 6), P1NP levels of the treatment group were also significantly (p<0.05) higher than the ones of control group. In accordance with the P1NP results, the ALP level of the treatment group was significantly (p<0.05) higher than the one of control group.CONCLUSION: Since bioscrew of green mussel shell-derived HA, PCL and PLA could increase the PINP associated early matrix synthesis, and ALP associated with later-stage mineralization, it can be concluded that bioscrew of green mussel shell-derived HA, PCL and PLA can be a promising material to promote bone repair.KEYWORDS: bone, HA, green mussel, bioscrew, P1NP, ALP, PCL, PLA